The challenges of women entrepreneurs in Malaysia: A systematic literature review - Iklima Husna Abdul Rahim; Dzulkifli Mukhtar; Siti Salwani Abdullah; Anis Amira Ab Rahman (Universiti Teknologi MARA, 2024)
This study aims to conduct empirical research on the challenges of women entrepreneurs in Malaysia, to emphasize the research topics that have yet to get attention, and to propose potential for further research. This study aimed to conduct a systematic literature review (SLR) on ten scholarly papers published between 2019 and 2023 and focused on women entrepreneurs in Malaysia. Ten themes underlie the empirical research on women entrepreneurs' challenges in Malaysia. These themes are as follows: work-life balance, technology factors, e-business adoption, perceived privacy, perceived security, ICT, limited access to financial resources, legal constraint, gender inequality and mentorship. The scope of this review is restricted to women entrepreneurs in Malaysia. Scopus and Google Scholar were the only two databases that made it onto the SLR. This study is one study to employ a systematic approach to provide a complete overview of the current status of the literature on the challenges of women's entrepreneurship research in Malaysia.